Effect of Hydrogel Additional Composition on Tablet Compose Based on Bio-Slurry - Muhammad Marzuki; Suwati Suwati; Muanah Muanah (Universitas Muhammadiyah Mataram, 2022)
Compost can be defined as the result of the decomposition of organic matter, while composting is a process in which organic matter is decomposed biologically, especially by microbes that utilize organic matter as an energy source. The effect of adding hydrogel to compost is a soil conditioner that focuses on water and nutrient retention so that it can reduce the use of irrigation water and increase the ability of plants to grow. The application of hydrogel and compost can improve physical properties such as bulk density, porosity, number of pores, water content of field capacity, water content of harvesting wilting point, available water, chemical properties, and soil biology. This study aims to determine the composition of the addition of hydrogel to tablet compost made from bio-slurry which is most appropriate for the moisture content and hardness of tablet compost. The method used in this research is experimental with direct testing in the laboratory. The results of the study The higher the addition of hydrogel, the higher the water content because there is still bound water trapped in the hydrogel and the best tablet compost or the highest water content was obtained in the P5 treatment, which was 18.35%, and the addition of hydrogel caused the tablet compost to become soft and elastic. so hardness is easier to destroy. The results of the analysis show that the best tablet compost hardness value is found at P0 of 97.0000 Newton